El poblado fronterizo de Tijuana, Emiliano Zapata y la revoluzione da tavolino - Samaniego López, Marco Antonio (El Colegio de México, A.C., 2017)
This article analyses the controversy between the Partido Liberal anarchists and their counterparts in Barre, Vermont, USA. It shows that the strategy followed by Ricardo Flores Magón and his followers was to invite Italian and Spanish anarchists to fight in Mexico and start the world revolution. Nevertheless, the arrival of fifty Italians to Tijuana, in May 1911, caused the opposite effect. These deemed the movement a revoluzione da tavolino, just in paper, made up by the writing of Ricardo Flores Magón. This discussion was taken up by the libertarian press in several places in the USA and Europe. Paradoxically, despite this dispute, both groups concluded that what happened in Tijuana was a movement staged by bandits from the USA, by cowboys and even marauders.